Dietary beta-glucans and mannanoligosaccharides improve growth performance and intestinal morphology of juvenile pacu Piaractus mesopotamicus (Holmberg, 1887) - Hisano, Hamilton; Soares, Michelly Pereira; Luiggi, Fabiana Golin; Arena, Arielle Cristina [UNESP] (Springer, 2018)
The objective of this study was to evaluate the effect of increased levels (0.0, 0.1, 0.2, 0.4, and 0.8%) of a combination of beta-glucans and mannanoligosaccharides (MOS) in isonitrogenous (23% of digestible protein) and isoenergetic (13.38 MJ of digestible energy kg(-1)) pacu diets, corresponding to five treatments and four replicates. A 30-day feeding trial was conducted to assess the effects on growth performance, hematological parameters, and intestinal morphology. Fish (n = 160, 30.92 +/- 0.46 g) were distributed randomly in 20 aquaria (300 L) with a recirculating water system with controlled temperature (26.20 +/- 0.32 degrees C) and fed four times a day until apparent satiation. A quadratic effect (P < 0.05) was observed for weight gain (WG), feed conversion ratio (FCR), and protein efficiency ratio (PER). The hepatosomatic and viscerosomatic indexes, hematocrit, hemoglobin, mean corpuscular volume (MCV), and mean corpuscular hemoglobin concentration (MCHC) did not show differences (P > 0.05) among treatments. Pacu fed beta-glucans and MOS at 0.1 and 0.2% resulted in the greatest (P < 0.05) villus height and perimeter. The diet containing 0.2% beta-glucans and MOS promoted the best growth response, feed efficiency, and intestinal morphology, without detrimental effects on the hematological parameters for juvenile pacu.
Keywords: Feed additive; Histology; Intestine; Polysaccharides; Prebiotic